The Development of ASE Furniture: Mobile Based Furniture Shopping Application - KHAIRUL NIZAM, AKIF; ZAINAL, NUREZAYANA (Applied Information Technology And Computer Science, 2025)
Furniture shopping has evolved significantly with the rise in e-commerce, offering customers greater convenience and accessibility. Arif Sufian Enterprise, a furniture store located in Kuala Sungai Baru, Melaka, has been operating offline for over three years, selling items such as closets, carpets, sofas, and beds. However, the absence of an online platform limits its audience reach and customer engagement. To address these challenges, this project aims to develop an Android mobile application using Flutter that includes modules for user account creation, online purchasing, and a loyalty program to reward returning customers. The Firebase database manages product inventories and user data, ensuring real-time synchronization and scalability. Initial testing demonstrates improved customer engagement, higher satisfaction, and enhanced accessibility compared to the store’s offline operations. This project successfully transitions Arif Sufian Enterprise into the digital marketplace, expanding its reach and modernizing its sales processes, thereby positioning the store competitively within the furniture e-commerce industry.